The psychological realism of disease literature in the story ‘‘The coughing couple’’ by Leopoldo Alas Clarín and the situation of COVID-19 patients - Gaber, Intidhar Ali (Al-Adab Journal, 2022)
The article describes the psychological reality of the characters in the story "The Coughing Couple", which is full of pain, emotion, and suffering from the epidemic. His characters use non-verbal language to express their feelings, which the author expresses in his own words to convey to the reader what his characters feel. The reason for choosing this topic is that it leads us to the same reality of psychological trauma that the COVID-19 pandemic currently affects all human societies on our planet. This psychological trauma is due to preventive social distancing and quarantine, which resulted in experience written transmitted in contemporary literary production.